2006
DOI: 10.1194/jlr.m500520-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive action of 2-hydroxyoleic acid in SHRs via modulation of the protein kinase A pathway and Rho kinase

Abstract: Olive oil consumption leads to high monounsaturated fatty acid intake, especially oleic acid, and has been associated with a reduced risk of hypertension. However, the molecular mechanisms and contribution of its different components to lower blood pressure (BP) require further evaluation. Here, we examined whether a synthetic, non-boxidation-metabolizable derivative of oleic acid, 2-hydroxyoleic acid (2-OHOA), can normalize BP in adult spontaneously hypertensive rats (SHRs) and whether its antihypertensive ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
3
32
0
1
Order By: Relevance
“…Indeed, this hypotensive effect can be reversed in rats by administration of the PKA blocker Rp-8-BrcAMP, which affects the last protein in this canonical signaling cassette (19). Together, these results indicate a direct relationship between the composition and structure of lipid membranes and BP regulation, which is supported by the relationships we have shown here.…”
Section: Molecular Mechanisms Involved In the Hypotensive Effects Of supporting
confidence: 78%
See 3 more Smart Citations
“…Indeed, this hypotensive effect can be reversed in rats by administration of the PKA blocker Rp-8-BrcAMP, which affects the last protein in this canonical signaling cassette (19). Together, these results indicate a direct relationship between the composition and structure of lipid membranes and BP regulation, which is supported by the relationships we have shown here.…”
Section: Molecular Mechanisms Involved In the Hypotensive Effects Of supporting
confidence: 78%
“…cyclase-cAMP/PKA that provokes a lowering of the BP and limits the effects of other vasoconstriction pathways (18,19). Accordingly, deficient AC activity in vascular cells, caused by altered G protein levels and function, diminishes intracellular cAMP levels, a hallmark of hypertension in humans (38,39) and in experimental animal models (30).…”
Section: Molecular Mechanisms Involved In the Hypotensive Effects Of mentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, we have recently demonstrated that an enhancement of the cAMP/PKA pathway in vascular tissue is responsible for the reduction of blood pressure observed in spontaneously hypertensive and normotensive SpragueDawley rats after 2-OHOA treatment. 11,33 In contrast, expression of COX8H and phosphorylation of CREB in rats treated with oleic acid declined to less than half of the levels of vehicle-treated control rats. This suggests that the high efficiency of 2-OHOA in the reduction of body weight is not caused by a simple potentiation of the activity of oleic acid but by a completely distinct mechanism.…”
Section: Effect Of C18 Fatty Acids On Body Weight O Vögler Et Almentioning
confidence: 92%